The accuracy of 2D ultrasound prenatal sex determination - Igbinedion, Blessing Ose-Emenim (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Pregnant women have been curious about the sex of their unborn child. The advent of ultrasound, its application into medicine, and the revolutionary changes in its resolution and function has led to the ability to assign a sex to these unborn children, thereby allaying the anxiety of these women but with consequent emergent ethical, moral, psycho-social, and medico-legal issues. The objectives were to determine the accuracy of sonographic prenatal sex determination, perform binary classification test, and the impact it has, including mis-diagnosis. MATERIALS AND METHODS: A prospective prenatal sonographic sex determination study on 205 consecutive consenting pregnant women aged 20-40 years in a private hospital in Benin between August 2010 and October 2011. Questionnaires were administered to these women before and after the scan and the women were told the sex of the fetuses and their feelings on the determined sex recorded. The sex at birth was confirmed and compared to the scan determined gender by their case note and telephone. Relevant discussions during the scan and later on were recorded on the questionnaires. The statistical package used was SPSS version 17 and binary classification tests were performed. RESULTS: The sensitivity (98.2%) and binary classification components values of prenatal sex determination were high with the sensitivity of detecting a female higher than that of males. Two males were misdiagnosed as females. Most of the women were happy even when the sex differed from that which they desired. CONCLUSION: Prenatal sonographic sex determination has a high sensitivity index. Consequently we advocate its use prior to more invasive sex tests.